Harnessing OLIG2 function in tumorigenicity and plasticity to target malignant gliomas - Kosty, Jennifer (Cell Cycle, 2017)
Glioblastoma (GBM) is the most prevalent and malignant brain tumor, displaying notorious resistance to conventional therapy, partially due to molecular and genetic heterogeneity. Understanding the mechanisms for gliomagenesis, tumor stem/progenitor cell propagation and phenotypic diversity is critical for devising effective and targeted therapy for this lethal disease. The basic helix-loop-helix transcription factor OLIG2, which is universally expressed in gliomas, has emerged as an important player in GBM cell reprogramming, genotoxic resistance, and tumor phenotype plasticity. In an animal model of proneural GBM, elimination of mitotic OLIG2(+) progenitors blocks tumor growth, suggesting that these progenitors are a seeding source for glioma propagation. OLIG2 deletion reduces tumor growth and causes an oligodendrocytic to astrocytic phenotype shift, with PDGFRα downregulation and reciprocal EGFR signaling upregulation, underlying alternative pathways in tumor recurrence. In patient-derived glioma stem cells (GSC), knockdown of OLIG2 leads to downregulation of PDGFRα, while OLIG2 silencing results in a shift from proneural-to-classical gene expression pattern or a proneural-to-mesenchymal transition in distinct GSC cell lines, where OLIG2 appears to regulate EGFR expression in a context-dependent manner. In addition, post-translational modifications such as phosphorylation by a series of protein kinases regulates OLIG2 activity in glioma cell growth and invasive behaviors. In this perspective, we will review the role of OLIG2 in tumor initiation, proliferation and phenotypic plasticity in animal models of gliomas and human GSC cell lines, and discuss the underlying mechanisms in the control of tumor growth and potential therapeutic strategies to target OLIG2 in malignant gliomas.